Liberalizing the Philippine mining industry: A CGE approach into analyzing its sectoral impacts on the economy - Castillo, Jesus Carlos Exequiel D. (Animo Repository, 2014)
The mining industry in the Philippines was once a promising venture that could contribute to the growth of output in the economy. Numerous legislations in support of mining in the Philippines that were passed through the years have proven ineffective in spurring development in the industry. Despite the spotted history of mining in the Philippines, the rising prices of precious metals in the world would seem that mining as a venue for output is as lustrous as ever. Due to the economic downturn in the mid 2000s, the markets turned their attention back to heavy investments in metals, causing most of them to hit their all-time highs. Unfortunately, mining in the Philippines is a noted underperformer during the periods of growth, which can be attributed to the fact that it is a young industry but with many concerns tied to it as well. Most of the concerns lie within the protection of the environment. The ISO guidelines to mining led many countries into levying taxes that would attribute to pollution and the Philippines is no exception. By using the 1994 input-output table for the Philippines and the Computable General Equilibrium model developed by Cororaton (2003), this study finds that the Mining Act of 1995 has negative welfare implications on households and different sectors. The government should reconsider some parts of the Mining Act of 1995, specifically the liberalization of investing in the industry; more particularly, allowing foreign-owned corporations to claim mineral rights in the country. Financial institutions may design instruments that will cater to the specific needs of the potential domestic investors. Mining firms, together with the government, should implement programs for the communities near areas with mineral exploration activities and other corporate social responsibility programs to spur economic development that is the ultimate goal of our country. © 2014 by De La Salle University, Manila, Philippines.